EFEKTIFITAS LAYANAN BIMBINGAN KELOMPOK DENGAN MEDIA CYNEMA THERAPHY UNTUK MENINGKATKAN SELF EFFICACY SISWA - Wulan Putriani; Arri Handayani; Mujiono (Melati Institute, 2023)
Research on the Effectiveness of Group Guidance Services with Cinema Therapy Media to Increase Self Efficacy of Class XI-3 SMA Negeri 1 Grobogan students is motivated by low self-efficacy in students, which will hinder actualization in their lives. As a result, students cannot achieve future goals. This self-efficacy will change easily and is strongly influenced by the development that is being gone through, especially for adolescents. This type of research is quantitative research with the quasi-experimental research method used is Nonequivalent Control Group Design. The population used in this study were 11th grade students of SMA Negeri 1 Grobogan. Based on the results of data analysis showed that the mean/average of the experimental group of 93.42 was greater than the mean of the control group of 53.42. Judging from the results of the calculation of paired sample t-test analysis to prove the research hypothesis, the value of Sig. (2-tailed) of 0.000 <0.05. If the significance value is smaller than 0.05, there is a difference from the pre-test and post-test results. This means that there is an influence of Cinema Theraphy media on Self Efficacy of students in class XI-3 SMA Negeri 1 Grobogan. It can be concluded that group guidance services with Cinema Theraphy media are effective for increasing Self Efficacy of students in class XI SMA Negeri 1 Grobogan, which has a significant difference, seen from the results of the t test calculation and the average pretest posttest results.